Leadership Talk A Discourse Approach to Leader Emergence - Walker, Robyn (Business Expert Press, 2014)
Traditionally, management theories have takena psychological approach to leadership, oftenassuming that it is a personality trait located withinan individual. In contrast, the discursive approach toleadership, which is the focus of this book, assumesthat leadership is created through communicationpractices.As a leader, this book will provide you with an in-depthlook at an emerging approach to the study ofbusiness leadership that focuses on language as avehicle for communicating leadership. The authorsexplore a new definition of leadership as the expressionof ideas in talk or in action that are recognizedby others as capable of progressing tasks or solvingproblems. The practical implication of this view ofleadership suggests that leaders must constantly enactand communicate their relationship to their followersin such a way as to be recognized by them asa leader. Inside, you and future leaders will learn howto approach leadership more effectively as a communicationpractice that involves and depends upon theresponse of potential followers